IMPROVING LISTENING ACHIEVEMENT THROUGH DICTOGLOSS TO THE TENTH GRADE STUDENTS OF SMA N 3 PALEMBANG - Dea ambarwati (Universitas Indo Global Mandiri, 2016)
The objective of the study was to find out whether or not Dictogloss is effective in improving students’ listening achievement to the tenth grade students of SMA N 3 Palembang. The method of the study was quasi – experimental design, non – equivalent control group design. The sample of this study was 40 students which was selected from class X Mipa 2 to be sample. The data were collected by using listening test which consisted of 50 questions. In analyzing the data, paired sample t-test and independent sample t-test were used. Based on the results of statistical analyses, it was found that t-obtained was 8.437, which was 0.05 of the level significance with the degree of freedom (df) 19 with the critical value of t-table 2.0930. so it can be concluded that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected, because t-obtained( -8.437) higher than t-table (2.0930) and significance level P (.000) was lower than α (0.05). it mean that there was significance difference between the tenth grade students of SMA N 3 Palembang who were taught through Dictogloss and those who were not. It also indicated that Dictogloss could improve the students’ listening achievement of tenth grade students of SMA N 3 Palembang. Key words : Improving, listening, and dictogloss.